CURRENT CIRCULAR ECONOMY ASPECT IN VALORIZATION OF AGRO-INDUSTRIAL WASTE AS VALUE-ADDED PRODUCTS - Đorđević, Tatjana; Vujetić, Jelena; Pintać-Šarac, Diandra (Food and Feed Research, 2024)
Agro-industrial waste has been considered to be a good source for the production of biofuels. Apart from that, it has also proven to be a valuable source of high-value-added products. The conversion of agro-industrial waste into high-value-added products allows the whole process to be designed in line with the biorefinery and zero-waste circular economy concept, especially because all parts of agro-industrial waste can be utilised. The application of the circular economy to agro-industrial systems is spreading globally and is a response to the current unsustainable model of production and consumption based on resource depletion and increased demand. This review provides a more detailed understanding of the potential of the circular economy as a response to the need to reduce the environmental impact of agro-industrial waste in organic production and to promote a more sustainable agri-food industry.
Keywords: circular bioeconomy; agro-industrial waste; lignocellulose; high-value products